2D Material‐Enabled Optical Rectennas with Ultrastrong Light‐Electron Coupling (Small 37/2022). Issue 37 (15th September 2022) - Nguyen, Hai‐Thai; Yen, Zhi‐Long; Su, Yen‐Hsun; Hsieh, Ya‐Ping; Hofmann, Mario
Abstract : Optical Rectennas In article number 2202199, Mario Hofmann and co‐workers present 2D materials–based gapped‐edge contacts that help realize efficient rectification of the optical field into direct current due to improved photon capture and conversion.